The effect of exercise on sleep habits of children with type 1 diabetic: a randomized clinical trial - Nastaran Amiri; Kimia Karami; Fatemeh Valizadeh; Yaser Mokhayeri (BMC, 2024)
Abstract Background Adequate sleep and exercise are important components of the human lifestyle. Paying attention to these two factors is very important to improve the condition of children with type 1 diabetes. Therefore, this study aimed to investigate the effect of exercise on sleep habits in children with type 1 diabetes. Material & methods 62 children with type 1 diabetes participated in this clinical trial. They will be divided into the intervention group (31) and the control group (31). Sleep habits were measured using the Children's Sleep Habits Questionnaire (CSHQ). All children's parents completed the CSHQ. The intervention for the experimental group consisted of 8 weeks of regular exercise program. The exercise program was prepared as an educational video and provided to parents. Paired sample t-test and ANCOVA test were used with SPSS 23. Results 62 children with an average age of 9.32 ± 2.02 were studied. Fifty-four and eight% of the children were girls and the rest were boys. The analysis of the variance test showed a significant difference (F = 144.72, P ≤ 0.01) between the average score of the sleep habits of the control group (62.45 ± 5.12) and the experimental group (47.06 ± 4.39). Conclusion Sleep habits in the experimental group improved after 8 weeks of exercise training using educational videos. Exercise as a non-pharmacological treatment is an effective way to manage diabetes and improve sleep quality in diabetic children.